Propidium iodide as an indicator of Giardia cyst viability. - Sauch, J F (1991)
The use of propidium iodide, whose uptake indicates cell death or damage, was investigated to assess the viability of heat-inactivated and chemically inactivated Giardia muris cysts. This was done by comparing propidium iodide staining with excystation. We first determined that propidium iodide could be used with an immunofluorescence detection procedure by showing that the percentages of Giardia lamblia cysts stained with this dye before and after subjecting them to a fluorescence detection method were similar. G. muris cysts were then exposed to heat (56 degrees C), 0.5 to 4 mg of chlorine per liter (pH 7.0, 5 degrees C), 0.1 to 10 mg of a quaternary ammonium compound per liter, or 2 mg of preformed and forming monochloramine per liter (pH 7.2, 18 to 20 degrees C). A good positive correlation between percent propidium iodide-stained cysts and lack of excystation was demonstrated for G. muris cysts exposed either to heat or to the quaternary ammonium compound. However, no significant correlation between absence of excystation and propidium iodide staining was found for cysts exposed to chlorine or monochloramines. These results demonstrate that the propidium iodide staining procedure is not satisfactory for determining the viability of G. muris cysts exposed to these two commonly used drinking water disinfectants.